SUSTAINABLE SUPPLY CHAIN MANAGEMENT AND DISRUPTIVE THEORY: A BIBLIOMETRIC REVIEW - BOWERS Dominique; MATLALA Ntswaki; BERHADIEN Moegamat; UMETOR Henry; GONGXEKA Thabo (Management of Sustainable Development)
Sustainable Supply Chain Management stands at the forefront of contemporary business strategies. Concurrently, the emergence of Disruptive Theory has reshaped conventional notions of supply chain dynamics, introducing innovative technologies and strategies that challenge traditional practices. This study investigates the impact of disruptive technologies on Supply Chain Management within emerging economies, with a specific emphasis on the South African context. The study addresses critical gaps in the field of technological readiness, which challenge the effective integration of disruptive technologies. Using bibliometric analysis, the study evaluated the contributions of academia, industry, and government to developing disruptive theory in supply chain management in South Africa. The study found a significant increase in research activity in 2022, with 71.6% of publications focusing on disruptive theory in supply chain management. The findings highlight the need for collaboration among academia, industry, and governmental bodies to advance disruptive theory in South African supply chain management and promote sustainability. Further, it provides a foundation for further exploration and development of strategies to overcome challenges and leverage opportunities in the rapidly evolving supply chain management landscape. Future researchers may explore a deductive research approach to understand how disruptive theory applies explicitly to the unique challenges and dynamics of the South African supply chain.